Angioplasty for coarctation of the aorta: A case series - Jnanaprakash B Karanth; R Ananthakrishnan; Ravi Kalra (Journal of Marine Medical Society, 2019)
Coarctation of the aorta (CoA) is a constriction of the thoracic aorta commonly located distal to the left subclavian artery. It is more common in males and is associated with Turner syndrome, bicuspid aortic valve, and ventricular septal defect. It presents as angina on exertion, lower limb claudication along diminished femoral pulses, and unequal limb blood pressure records. Balloon angioplasty with or without stenting is the preferred treatment in native coarctation or recoarctation after surgery. Here, we report four cases that were successfully managed with balloon aortoplasty for CoA.